Bahasa Indonesia Mbah KH. Imam Puro Purworejo pilar pendukung pembelajaran di Madrasah Ibtidaiyah (MI) Imam Puro Lubangindangan kecamatan Butuh kabupaten Purworejo: Bahasa Indonesia - Sholihah, Tsaniyatus (Maliki Interdisciplinary Journal, 2023)
This research focuses on the role of Mbah Imam Puro Purworejo in the Imam Puro Lubangindangan Purworejo Elementary School (Madrasah Ibtidaiyah or MI). Mbah Imam Puro plays a crucial role in the educational institution in Purworejo, particularly in the MI Imam Puro Lubangindangan Purworejo. This study will primarily focus on Mbah Imam Puro's role or efforts, the history of MI Imam Puro Lubangindangan Purworejo, and Mbah Imam Puro's significance as a pillar for the development of the school up to the present time. The information and data for this research will be collected using a qualitative descriptive method. This study will reveal the endeavors carried out by Mbah Imam Puro in supporting various madrasahs in Purworejo, including MI Imam Puro Lubangindangan Purworejo. It will also highlight the continuous progress of MI Imam Puro Lubangindangan Purworejo, with Mbah Imam Puro remaining a driving force behind its advancement.